WaSH as a maternal health issue: three perspectives from rural Uganda. Issue 2 (17th February 2019) - Schuster-Wallace, Corinne; Watt, Susan; Mulawa, Zachariah; Pommells, Morgan
ABSTRACT: Inadequate water, sanitation, and hygiene (WaSH) knowledge and practices affect maternal and newborn morbidity and mortality. This article describes postpartum knowledge, resources, and practices in three rural Ugandan hospitals. A lack of WaSH resources was problematic for both staff and newly-birthed mothers who demonstrated a lack of knowledge about the appropriate use of WaSH resources and the links between WaSH and health protection. These results suggest that in addition to increasing the availability of medical interventions, basic preventative public health practices should be reflected in policy and practice integrated across the spaces inhabited by pregnant women to achieve improved maternal and newborn outcomes.